Analysis of a Three-Dimensional Multilevel Parking Using Analysis Tool - Rajan Kushwaha; Anita Chaturvedi; Pradeep Nirmal (International Journal of Scientific Research in Civil Engineering, 2024)
Parking is a critical component of transportation policy and management for any locality especially for the large central cities. The policies and management practices affecting parking lead to outcomes that, in turn, can affect land use, air quality, traffic congestion, travel behaviour, safety, and economic development, not to mention revenue lines. Yet, effectively managing parking is an ongoing battle for the large central cities as they face competing, and sometimes contradictory, objectives along with an ever increasing demand for space.Multi level Smart parking is proposed with a structure G+4 and the designing of the structure is done using computer aided applications namely Autodesk Autocadd and Autodesk 3d Max and analyzed the structure considering seismic zone as per I.S. 1893-I:2016 using Bentley Staad.Pro. Bhopal is ranked on 20th number in calculus of traffic congestion. The results stated Building displacement was found to be within permissible limit in all direction, hence safe in seismic hazards. Unbalance forces are observed linear in all the stories as sections adopted are safe in designing. Vertical forces are observed linear in distribution of load. Bending moment is observed linear in all the storey which will provide linear requirement of steel in the RCC members